The development of 3D model building information modelling (BIM) for commercial office building - Nur 'Atiqah, 'Ashri (2018)
This thesis investigate the influence of Building Information Modelling in the building project interpretation and how this technology may enhances construction process effectively. There are 5 different 3D models that can be developed using BIM software(s). Autodesk Revit is a BIM software used to develop the five models which they are; Architectural model, Structural model, Mechanical model, Electrical model and Plumbing model but for this study will only cover Architectural model and Structural model. These models were coordinated and appended together to test BIM implementation. Three BIM utilization activities: visualization, efficiency process and data management. The utilization of these applications in construction showed that: (1) Deficiency on develop the process of construction project into complete building. It helps all parties can work together on develop the process be more efficiently as all parties are using the same software. (2) The visualization is generally the simplest use of a Building Information Model such as elevation and cross-section view in 3D model. As visualization is simplest it is also a great application because it enhances the overall outcome of any project. (3) Improve Data Management in Construction Industry. This helps to in improving the data management in construction to be access faster. In conclusion, BIM technology helps to improve coordination among parties, visualization, and data management.